Probing the Hepatic Progenitor Cell in Human Hepatocellular Carcinoma - Shu-Qin Jia; Jian-Jun Ren; Pei-De Dong; Xing-Kai Meng (Gastroenterology Research and Practice)
Objective. The intrahepatic stem cells, also known as hepatic progenitor cells (HPCs), are able to differentiate into hepatocytes and bile duct epithelia. By exposure of different injuries and different hepatocarcinogenic regimens, the mature hepatocytes can no longer effectively regenerate; stem cells are involved in the pathogenesis of hepatocellular carcinoma. Methods. Immunohistochemistry was performed on 107 paraffin-embedded hepatocellular carcinoma specimens with the marker of hepatocyte and hepatocellular carcinoma (HepPar1), biliary differentiation (CK7,CK19), haemopoietic stem cell (HSC) (c-kit/CD117, CD34, and Thy-1/CD90), HPC specific markers (OV-6), and Ki-67, p53 protein. Results. HPCs can be identified in the tumor nodules, around the edge of tumor nodules, and in the portal tracts of the paracirrhosis nodules being positive in HepPar1, CK7, CK19, and OV-6, but they failed to immunostain with CD117, CD34, and CD90. The HPCs positive in Ki-67 are observed in the tumor and paracirrhosis tissues. In 107 specimens, 40.2% (43/107) HCC tissues expressed p53 protein, lower than that of the HPCs around the tumor nodules (46.7%, 50/107) and much higher than that of the HPCs around the paracirrhosis nodules (8.41%, 9/107). Conclusion. Human hepatocellular carcinogenesis may be based on transformation of HPCs, not HSCs, through the formation of the transitional cells (hepatocyte-like cells and bile ductal cells).